2020
DOI: 10.1002/joc.6553
|View full text |Cite
|
Sign up to set email alerts
|

Climate change projections for the Worldwide Bioclimatic Classification System in the Iberian Peninsula until 2070

Abstract: Climate change projections for the four major divisions of the Worldwide Bioclimatic Classification System in the Iberian Peninsula (IP) are analysed using a six‐member ensemble (EURO‐CORDEX) for 1961–1990, 1981–2010, 2011–2040, and 2041–2070 periods for RCP4.5 and RCP8.5. The direct forcing method was used to correct the bias of the simulated data using an observational gridded dataset (E‐OBS). Results show a decrease of the temperate areas in the north‐western region of the IP, with higher expression in RCP8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 64 publications
5
18
0
Order By: Relevance
“…The heterogeneity of the spatial patterns in the future, under both RCPs, also suggests changes in the large-scale patterns of daily precipitation in IP that were already identified in the past [60]. Furthermore, the upward trend in the dry events is projected to be strengthened in future climates, which is also in agreement with previous studies with related impacts on droughts [61], bioclimatic conditions [62], or climate classification [21,63]. Since droughts have deep impacts on water resources, agriculture, and the environment, this is particularly relevant.…”
Section: Discussionsupporting
confidence: 88%
“…The heterogeneity of the spatial patterns in the future, under both RCPs, also suggests changes in the large-scale patterns of daily precipitation in IP that were already identified in the past [60]. Furthermore, the upward trend in the dry events is projected to be strengthened in future climates, which is also in agreement with previous studies with related impacts on droughts [61], bioclimatic conditions [62], or climate classification [21,63]. Since droughts have deep impacts on water resources, agriculture, and the environment, this is particularly relevant.…”
Section: Discussionsupporting
confidence: 88%
“…However, four additional ombrothermic indices are also computed: the ombrothermic index of the hottest month of the summer quarter (Ios1), the ombrothermic index of the hottest two months of the summer quarter (Ios2), the ombrothermic index of the summer quarter (Ios3) and the ombrothermic index of the 4 months resulting from adding the summer quarter and the month immediately preceding it (Ios4). Further details can be found in Rivas-Martínez et al [23,24], while a summary of the main equations can be found in Andrade and Contente [11]. In this Table, CI is the continentality index, TI is the thermicity index and TIc is the compensated thermicity index, Tp is the annual positive temperature (tenths of °C), when the mean monthly temperature is higher than 0°C.…”
Section: Worldwide Bioclimatic Classification System (Wbcs)mentioning
confidence: 99%
“…Climate change has already deeply impacted biodiversity, ecosystems, and agroforestry systems [9][10][11]. Global warming and changes in the precipitation patterns are fostering an increase in arid/dry regions, and ultimately the expansion of desertic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has already deeply impacted biodiversity, ecosystems, and agroforestry systems [9][10][11]. Global warming and changes in the precipitation patterns are and between 1990-2018 are presented.…”
Section: Introductionmentioning
confidence: 99%